Agroforestry systems for biodiversity and ecosystem services: the case of the Sibundoy Valley in the Colombian province of Putumayo. Issue 1 (1st January 2017) - Palacios Bucheli, Vandreé Julián; Bokelmann, Wolfgang
ABSTRACT: The Camëntsá and Inga indigenous communities of the Sibundoy Valley, in the Colombian province of Putumayo, employ agroforestry systems for their livelihoods. The objectives of this enquiry are (1) to understand the importance of the biodiversity within agroforestry systems, as providers of provisioning, regulating, and cultural ecosystem services to indigenous households and (2) to assess the importance of protecting biodiversity through agroforestry systems to ensure food security. The study employed a qualitative research strategy involving participant observation and semi-structured interviews. It describes the ecosystem services delivered within the agroforestry systems and the uses given by the communities to their related biodiversity. A total of 21 uses were identified for 128 species. The provision of food, natural medicine and biochemicals, fuel, and fibres was the most important final services derived from that biodiversity. Additionally regulating and cultural ecosystem services accounted for almost one-third of the total uses of the species. Based on its findings, the study highlights the need to maintain both the agroforestry systems and their biodiversity to ensure the delivery of all three ecosystem services and the communities' food security and livelihoods.EDITED BY John Parrotta